Service Quality and Public Satisfaction at Labuhanbatu Civil Registry: Kualitas Pelayanan dan Kepuasan Masyarakat di Disdukcapil Labuhanbatu - Aulia, Dini; Nasution, Novrihan Leily; Gulo, Nur’ainun (Academia Open, 2026)
General Background: Public administrative services play a crucial role in fulfilling citizens’ rights related to population documents and require quality-oriented delivery to achieve public satisfaction. Specific Background: The Population and Civil Registration Office of Labuhanbatu Regency provides various administrative services but faces challenges such as service queues, processing time, and adaptation to digital services. Knowledge Gap: Previous studies tend to examine public service quality and satisfaction in general terms, with limited focus on the interaction between service quality dimensions and evolving community needs, particularly in the context of digital transformation at the regional level. Aims: This study aims to analyze the relationship between service quality and public satisfaction in population administration services. Results: Using a quantitative approach with 60 respondents and simple linear regression, the findings show a regression equation of Y = 26.704 + 0.345X, with t-value 3.119 > 1.984 and significance 0.003 < 0.05, indicating a significant relationship. The coefficient of determination (R² = 0.144) reveals that service quality contributes 14.4% to public satisfaction, while other factors account for 85.6%. Novelty: This study integrates service quality analysis with digital service context and identifies specific service experience factors affecting satisfaction at the local administrative level. Implications: The findings suggest the need for comprehensive service improvement, including responsiveness, service speed, accessibility, and digital service development to support effective public service policies. Highlights• Service assessment classified as good based on respondent evaluation• Statistical testing confirms significant relationship between variables• Contribution value indicates presence of additional determining factors KeywordsService Quality; Public Satisfaction; Public Service; Population Administration; Civil Registration